2004
DOI: 10.1007/s10832-004-5195-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonstoichiometry and Defect Chemistry in Praseodymium-Cerium Oxide

Abstract: Praseodymium cerium oxide (Pr x Ce 1−x O 2−δ ) is a mixed ionic-electronic conductor with high levels of nonstoichiometry under oxidizing conditions resulting from reduction of Pr 4+ to Pr 3+ . Coulometric titration measurements performed on (Pr x Ce 1−x O 2−δ ) with x = 0.2 are generally consistent with those derived from electrical conductivity measurements. Nevertheless, a somewhat larger degree of nonstoichiometry measured via coulometric titration implies that non-charged defect species may be significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 3 publications
5
34
1
Order By: Relevance
“…19. Another study 20 performed at lower temperatures, 600-750°C, at the P O 2 range between 10 −5 and 10 −1 atm suggested ideal behavior. However, the examined powder was nanosized, which significantly alters the reduction properties.…”
Section: Ideal Model: the Reduction Of Pr And Ce Is Treated In An Idementioning
confidence: 93%
“…19. Another study 20 performed at lower temperatures, 600-750°C, at the P O 2 range between 10 −5 and 10 −1 atm suggested ideal behavior. However, the examined powder was nanosized, which significantly alters the reduction properties.…”
Section: Ideal Model: the Reduction Of Pr And Ce Is Treated In An Idementioning
confidence: 93%
“…The introduction of more easily reduced cations such as Pr or Tb into ceria allows the material to begin to reduce even under oxidizing conditions. 6,7 In recent publications, the authors of this work reported in detail on the defect, 7-9 transport, 7,9,10 optical, 11 and mechanical [12][13][14] properties of Pr x Ce 1Àx O 2Àd (PCO) with x 5 0.1. Some of the important features of Pr 0.1 Ce 0.9 O 2Àd include the introduction of MIEC behavior under oxidizing conditions; sample coloration, connected with the formation of a Pr-based impurity band; as well as chemical expansion accompanied by a decrease in the energy needed to form oxygen vacancies with reduction.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of x = 0.2 and at 700 • C, t ion was found to be 0.6 under a pO 2 gradient between 1.01 × 10 5 Pa and 0.21 ×10 5 Pa [11]. The mixed conductivity of Ce 1−x Pr x O 2 was also confirmed by the pO 2 dependence of total conductivity by Stefanik and Tuller [10]. For CPO-xMFO, the small decrease in the oxygen permeability in the range of less than 5 vol% MnFe 2 O 4 seems to be attributed to decrease in Pr content in the matrix ceria phase as a result of the formation of PrFeO 3 phase as mentioned above.…”
Section: Resultsmentioning
confidence: 84%
“…Unlike Gd or Sm-doping, Prdoping raises both ionic and electronic conductivities of CeO 2 [10]. This increase in mixed conductivity is favorable for oxygen permeable ceramics.…”
Section: Introductionmentioning
confidence: 99%